Types of Implicature in The Paper Towns Movie - Ani, Fitri; Heridayani, Heridayani; Sari, Nurmaliana; Afkar, Rijalul (MUDABBIR Journal Research and Education Studies, 2024)
Implicature is the study about how to understand the speaker's meaning which is stated indirectly. This study deals with conversational implicature found Paper Towns movie script in John Green's movie. The objectives of the study is to analyze the types of implicature. The qualitative research was used in this research. Grice's conversational implicature was applied in analysing the data. The source of data is the conversation between the characters Quentin and Margo which taken from the Paper Towns movie script written by John Green. The data of this study were taken from the transcript of the utterances  of the characters in Paper Towns movie script written by John Green which related to implicature. Those utterances were transcribed and analyzed in order to answer the research question, that is the types of implicature used. The results showed that there were two types of conversational implicature used by the characters, namely: generalized conversational implicature and particularized conversational implicature.